Upper Plate Heterogeneity Along the Southern Hikurangi Margin, New Zealand. Issue 4 (13th February 2020) - Henrys, Stuart; Eberhart‐Phillips, Donna; Bassett, Dan; Sutherland, Rupert; Okaya, David; Savage, Martha; Evanzia, Dominic; Stern, Tim; Sato, Hiroshi; Mochizuki, Kimihiro; Iwasaki, Takaya; Kurashimo, Eiji; et al.
Abstract: Controlled and natural source seismic data are used to build a 3‐D P wave model for southern North Island, New Zealand, where the Pacific Plate subducts beneath the Australian Plate at a rate of ~41 mm/year. Our analysis reveals an abrupt along‐strike transition in overthrusting plate structure within Cook Strait. Contrasts in properties (Vp, Vp/Vs, and Qs) likely reflects the degree of deformation in the Australian Plate, where the Alpine‐Wairau and Awatere Faults mark the northern boundary of a terrane that has undergone >50° of clockwise vertical‐axis rotation since the early Miocene. Heterogeneity of the crustal transition is likely associated with changes in frictional and elastic properties that may impact elastic stress accumulation and inhibit southward propagation of megathrust earthquakes. Low connectivity of faults in Cook Strait is consistent with the heterogeneity we observe and may promote complex earthquake triggering by lateral stress loading during earthquakes or slow slip events. Plain Language Summary: Subduction zones produce the largest earthquakes and tsunami on Earth and knowledge of structures and physical rock properties at subducting margins will inform how and where strain is accumulated, as well as how stress is relieved. Combined information from earthquakes, seismic data, gravity observations, and geological mapping constrain a new 3‐D subduction zone image at the southern Hikurangi margin, central New Zealand, where the Pacific Plate dives beneath the Australian Plate. The image reveals an abrupt inherited along‐strike transition in the upper Australian Plate structure through Cook Strait. The region is notable because the 2016 magnitude 7.8 Kaikōura earthquake ruptured more than a dozen faults in northern South Island, south of Cook Strait, and triggered large afterslip on the subduction interface. However, the Kaikōura earthquake afterslip did not extend across the Cook Strait transition, into the southern North Island, where the subduction interface is currently strongly coupled or locked. Our work offers new insights suggesting that structure and frictional properties of the overthrusting upper plate might also limit the lateral extent of rupture in future earthquakes on the southern Hikurangi subduction zone. Key Points: The 3‐D velocity images and residual gravity anomalies reveal along‐strike transition in upper plate structure along southern Hikurangi margin Transition marks the northern boundary of a tectonic terrane that has undergone clockwise vertical‐axis rotation since early Miocene The structure and frictional properties of the upper plate may control megathrust coupling and seismogenic behavior in southern Hikurangi